The Evolution Relationship Between Intensive Land Use and Land Ecological Security in the Urban Agglomeration in the Northern Slope of the Tianshan Mountains, Northwest China - Xianwei Zhu; Jianming Ye; Mengmeng Zhu; Zhe Gao; Miaomiao Li; Mei Wang; Yingbin Li (Land)
Revealing the relationship between intensive land use (ILU) and land ecological security (LES) is crucial for achieving high-quality land resource development and ensuring the sustainability of land ecosystems, especially in arid regions with fragile human–land relationships. In this study, we evaluated ILU and LES in the urban agglomeration on the northern slope of the Tianshan Mountains (UANSTM) and analyzed the evolution of ILU and LES using Pearson correlation analysis, four-quadrant model, and coupling coordination degree model. The results indicated that from 2012 to 2022, ILU and its three subsystems generally showed an upward trend in the UANSTM, with an average annual growth rate of 2.96%, 2.50%, 3.32%, and 0.289%, respectively, and with ILU levels significantly higher in the eastern and central counties compared to other areas. LES and its three subsystems also exhibited a general increase, with average annual growth rates of 1.63%, 0.86%, 3.10%, and 1.51%, respectively, although high-level areas displayed distinct spatial variations. The Pearson correlation analysis showed that the land input level had a significant negative effect on the pressure, but the positive effects of state and response enhanced the LES. The number of double-high cities increased significantly from 1 to 6, and the number of double-low cities decreased from 6 to 0. Compared with other cities and counties, the LES-lagging counties and cities faced the challenge of coordinating urban development and ecological conservation. While coupling coordination levels across all counties improved to varying degrees, none reached the optimal coordination stage. The findings and methodologies of this study provide helpful insights into human–land relationships in arid regions, supporting the goals of high-quality urban development and sustainability.